The Temple Section in Mark (Mk 11-12): An Introduction to the Passion Narrative - Edayadiyil, George (Asian Horizons, 2020)
The doctoral dissertation of Dr Fr John Kallikuzhuppil CMI titled The Temple Section in Mark (Mk 11-12), An Introduction to the Passion Narrative, is the result of many years of serious study and research done by Dr John under the guidance of Prof Albert Vanhoye, SJ, at the prestigious centre of biblical studies, Biblicum, Rome. This work is a thorough redaction critical analysis of the possible correlation between the Temple section (11:1-12:44) and the Passion Narrative (14:1-16:8) in the Gospel of Mark from a thematic, structural and literary perspective. The study is also undertaken to know whether the above narratives form an organic whole in the Gospel of Mark. The research further tries to highlight the unique style, composition, vocabulary and the motif of Mark in comparison with other synoptic gospels and the Gospel of John. Even though this research was completed in 1982, even today it is a very relevant, meaningful and useful study material for any serious reader and scholar on the book of Mark and for those who are interested to know the reason for the death of Jesus from the primary source coming from Mark. The book is a great contribution in biblical scholarship and the understanding of Christian faith from the perspective of the mystery of Christ, the master story of the New Testament. Dr Fr John Kallikuzhuppil CMI, The Temple Section in Mark (Mk 11-12), An Introduction to the Passion Narrative, Bengaluru: Dharmaram Publications, 2020. Pages: xxi+394. ISBN 978-81-945014-0-4.